Answer:
![y^{\frac{3}{2}](https://tex.z-dn.net/?f=y%5E%7B%5Cfrac%7B3%7D%7B2%7D)
Step-by-step explanation:
Let ![m=\sqrt{y^3}](https://tex.z-dn.net/?f=m%3D%5Csqrt%7By%5E3%7D)
![m=(y^3)^{\frac{1}{2}}\\\\m=y^{3\times \frac{1}{2}}\ \ \ \ \ \ \ \ \ [as\ (x^a)^b=x^{ab}]\\\\m=y^{\frac{3}{2}](https://tex.z-dn.net/?f=m%3D%28y%5E3%29%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%5C%5C%5C%5Cm%3Dy%5E%7B3%5Ctimes%20%5Cfrac%7B1%7D%7B2%7D%7D%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5Bas%5C%20%28x%5Ea%29%5Eb%3Dx%5E%7Bab%7D%5D%5C%5C%5C%5Cm%3Dy%5E%7B%5Cfrac%7B3%7D%7B2%7D)
Answer:
7 _> x
Step-by-step explanation:
28 - x _> 7(x-4)
28 - x _> 7x-28
28+28 _> 7x+x
56 _> 8x
7 _> x
Step-by-step explanation:
x(x-3)=0
x=0 or (x-3) =0
x= 0 or x =3
The test That holds true for this inequality is given as 1/4 and 1
<h3>How to solve for the inequality</h3>
3/2 y - 2x > 1
The goal is to make y the subject
then
3/2 y > 2x + 1
We have to divide through the equation by 3/2
Such that y > 4/3 x + 2/3
Read more on inequality here: brainly.com/question/25275758
#SPJ1